2022
DOI: 10.1002/pdi.2415
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of severe hypoglycaemia requiring hospital admission: a retrospective study

Abstract: This is a retrospective study intended to determine the prevalence of severe hypoglycaemia requiring admission to Mater Dei Hospital from January to December 2018. We identified risk factors associated with hospital admission and conducted a survival analysis of the cohort.All patients admitted with diabetes and hypoglycaemia were identified by means of hospital admission database, clinical notes, discharge summaries and iSOFT clinical manager. A Cox regression model and a multivariate analysis were utilised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Ultimately, 35 studies met the pre-defined inclusion criteria , of which 8 studies were identified through citation analysis. Studies were published between 2005 and 2023 and conducted mainly in the United States (US) (n = 7) [24,26,36,42,47,49,52], Italy (n = 6) [23,29,31,33,41,53], Korea (n = 4) [30,38,48,55], Denmark (n = 2) [45,46], Germany (n = 2) [25,43], Greece (n = 2) [22,28], Japan (n = 2) [37,56], Portugal (n = 2) [35,44], Taiwan (n = 2) [32,50], Malta (n = 1) [51], Pakistan (n = 1) [27], France (n = 1) [54], Spain (n = 1) [39], Thailand (n = 1) [40], and the United Kingdom (UK) (n = 1) [34].…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately, 35 studies met the pre-defined inclusion criteria , of which 8 studies were identified through citation analysis. Studies were published between 2005 and 2023 and conducted mainly in the United States (US) (n = 7) [24,26,36,42,47,49,52], Italy (n = 6) [23,29,31,33,41,53], Korea (n = 4) [30,38,48,55], Denmark (n = 2) [45,46], Germany (n = 2) [25,43], Greece (n = 2) [22,28], Japan (n = 2) [37,56], Portugal (n = 2) [35,44], Taiwan (n = 2) [32,50], Malta (n = 1) [51], Pakistan (n = 1) [27], France (n = 1) [54], Spain (n = 1) [39], Thailand (n = 1) [40], and the United Kingdom (UK) (n = 1) [34].…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…In terms of study orientation, the majority were retrospective studies (n = 29), with study designs varying from analytical cross-sectional (n = 16) [22,24,[29][30][31]33,35,40,43,48,[50][51][52][53]55,56], cohort (n = 10) [25,26,32,34,36,41,42,46,47,49], prevalence (descriptive crosssectional) (n = 6) [23,27,37,39,44,54], to case-control (n = 3) [28,38,45]. Most studies (60%) were rated as being high quality (Tables S4-S7) [23,24,30,32,[35][36][37][38][39][40][41][43][44]…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations